2015
DOI: 10.1002/adhm.201500323
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light‐Triggered On‐Demand Drug Release from Hybrid Hydrogels and its Application in Transdermal Patches

Abstract: On-demand release from stimuli-responsive hydrogels has received great attention due to an increasing clinical need. Here, we have prepared spherical hydrogel beads showing visible light-induced volume change at body temper-ature. By spray injection of the monomer solution using the alginate templ-ating method, hybrid beads of several hundred micrometers, consisting of temperature-responsive poly(N-isopropylacrylamide-co-vinyl-2-pyrrolidinone) hydrogel and magnetite nanoparticles (MNP), are produced. MNP dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 35 publications
0
50
0
Order By: Relevance
“…The visible light triggered release of adsorbed ions/molecules from the surface of nanoparticles could open a wide range of novel applications including drug delivery, sedimentation, desalination, change in pH, optical devices based on ionic dyes and sensing. 1,2 Light can be further used to induce the mechanical response of materials 3,4 or fluorescence switching which is applicable in sensors and fluorescent logic devices. [5][6][7] Access to this untapped abundant source of energy offers a safe, easy and readily accessible means to switch-on or switchoff different phenomena.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The visible light triggered release of adsorbed ions/molecules from the surface of nanoparticles could open a wide range of novel applications including drug delivery, sedimentation, desalination, change in pH, optical devices based on ionic dyes and sensing. 1,2 Light can be further used to induce the mechanical response of materials 3,4 or fluorescence switching which is applicable in sensors and fluorescent logic devices. [5][6][7] Access to this untapped abundant source of energy offers a safe, easy and readily accessible means to switch-on or switchoff different phenomena.…”
mentioning
confidence: 99%
“…Some release mechanisms include a tailored polymer to favor release, but most release triggers are coupled to nanoparticles that activate delivery. 1 The most eloquent release mechanism involves the change in the conformation of organic compounds, from one isomer to another after exposure to UV light, 2,3 thereby altering the molecule's adsorption affinity. This is restrictive to a limited number of transportable molecules.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the hydrogel was designed to induce sharp volume phase transition slightly above the body temperature by copolymerization of VP with NIPAm. In our previous study, we revealed that the incorporating hydrophilic VP moieties into the PNIPAm chain lead to the increase of LCST17. For the shell formation, AA was added as amine source for conjugating FA through amide coupling and bisAA was used as the crosslinker.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, magnetite (iron oxide) nanoparticles, which produce a photothermal response with visible light irradiation, were added to NiPAAm microgels. These microgels were encapsulated inside alginate hydrogels and further incorporated into PDMS skin patches for transdermal drug delivery [96]. Typically, transdermal drug-delivery systems are used for long-term delivery and are unable to achieve immediate release when drug action is needed.…”
Section: Micro-and Nano-particlesmentioning
confidence: 99%